E-Commerce Group Buying Web-based System - Wan Nur Izreen Shuhada Wan Hussin; Mohamad Aizi Salamat (Applied Information Technology And Computer Science, 2022)
E-Commerce Group Buying Web-based System is a web-based system that is developed for Malaysian’s user to make the online purchasing by group easily, and compatible for web and mobile application platform. Recently, in Malaysia, e-commerce group buying website is not very familiar and not well-known as the other countries like China. The study has been conducted on existing group purchasing system in Malaysia, which is Groupon Malaysia. One of the problems encountered by the user that use this e-commerce website is the technology used by the system is incompatible for mobile platform user, make it having difficulties to growth well in e-commerce industry. Thus, the system should be able to develop a web-based system that enable Malaysian user to use it in pc or mobile to make it convenient for the user when dealing with online shopping. Furthermore, this study focusses on developing e-commerce group buying web-based system by using SCRUM agile methodology and object-oriented programming (OOP) approach for the system analysis and design. Therefore, the system is designed as a web-based online group buying platform that allows Malaysian users to make group purchases at a low-price rate with minimal effort without having to go to a physical store.